Power Base of Unmanned Aerial Vehicles - A. A. Laptsevich; L. I. Grechihin; N. G. Kutz (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A molecular-kinetic approach to an analysis of thermal energy converters has been developed in the paper. The approach allows to carry out a computer simulation under various conditions of converter application. The paper considers possibilities to improve heat engines and electro-dynamic motors. It has been revealed that an increase of the UAV flight time can be achieved not only through an efficient usage of energy generated during fuel combustion but also through arrangement of open power systems that implement a heat pump principle. A prospect concerning energy development of transport facilities is to create interconnected systems of open-type with application of heat pumps.